Ukrainian Antarctic Bibliography: Publications in 2016–2018 - Videnina, N.G.; Rybachuk, V.P.; Fedchuk, A.P.; Prymachenko, S.I.; Petrenko, N.S. (Український антарктичний журнал, 2018)
Objectives of the study is to monitor the modern national scientific literature on Antarctic research, first of all, as an element of systematic information and bibliographic as well as scientometric support for the implementation of state scientific and technical programs.